Impact of left ventricular function on clinical outcomes among patients with coronary artery disease. (August 2019) - Siontis, George CM; Branca, Mattia; Serruys, Patrick; Silber, Sigmund; Räber, Lorenz; Pilgrim, Thomas; Valgimigli, Marco; Heg, Dik; Windecker, Stephan; Hunziker, Lukas
Aims: To investigate the clinical relevance of contemporary cut-offs of left ventricular ejection fraction (LVEF) including an intermediate phenotype with mid-range reduced ejection fraction among patients with coronary artery disease undergoing percutaneous coronary intervention. Methods and results: Patient-level data were summarized from five randomized clinical trials in which 6198 patients underwent clinically indicated percutaneous coronary intervention in different clinical settings. We assessed all-cause mortality as primary endpoint at five-year follow-up. According to the proposed LVEF cut-offs, 3816 patients were included in the preserved LVEF group (LVEF ≥ 50%), 1793 in the mid-range reduced LVEF group (LVEF 40–49%) and 589 patients in the reduced LVEF group (LVEF < 40%). Patients in the reduced LVEF group were at increased risk for the primary outcome of all-cause mortality compared with both, preserved and mid-range LVEF throughout five years of follow-up (adjusted hazard ratio 2.39 (95% confidence interval 1.75–3.28, p < 0.001) and 1.68 (95% confidence interval 1.34–2.10, p < 0.001), respectively). The risk of cardiac death and the composite endpoint of cardiac death, myocardial infarction, or stroke were higher for patients in the reduced LVEF group compared with the preserved and mid-range reduced LVEF groups, but also for the mid-range LVEF compared with preserved LVEF group (adjusted p < 0.05 for all comparisons) throughout five years. Irrespective of clinical presentation at baseline (stable coronary artery disease or acute coronary syndrome), patients with reduced or mid-range LVEF were at increased risk of all-cause mortality and cardiac death up to five years compared with the other group (adjusted p < 0.05 for all comparisons). Conclusion: Patients with reduced LVEF <40% or mid-range LVEF 40–49% in the context of coronary artery disease undergoing clinically indicated percutaneous coronary intervention are at increased risk of all-cause mortality, cardiac death and the composite of cardiac death, stroke and myocardial infarction throughout five years of follow-up. The recently proposed LVEF cut-offs contribute to the differentiation and risk stratification of patients with ischaemic heart disease.